2022
DOI: 10.3390/ijms23179729
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Sodium Nitroprusside Mitigates Lead Toxicity in Rice by Regulating Antioxidants and Metal Stress-Related Transcripts

Abstract: Sustainable agriculture is increasingly being put in danger by environmental contamination with dangerous heavy metals (HMs), especially lead (Pb). Plants have developed a sophisticated mechanism for nitric oxide (NO) production and signaling to regulate hazardous effects of abiotic factors, including HMs. In the current study, we investigated the role of exogenously applied sodium nitroprusside (SNP, a nitric oxide (NO) donor) in ameliorating the toxic effects of lead (Pb) on rice. For this purpose, plants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…SNP restored 10 µM Hg-induced depletion of AsA and thiols in wild-type Arabidopsis roots (which were directly in contact with the treatment solution), but not in leaves [ 22 ]. Cross-talk between SNP and heavy metal Cd led to an increase in AsA amount over single treatments in the green microalga [ 16 ], and cross-talk between SNP and Pb lowered oxidative stress markers and enhanced the antioxidant system in rice [ 23 ], indicating a similar positive effect of SNP in various plant lineages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP restored 10 µM Hg-induced depletion of AsA and thiols in wild-type Arabidopsis roots (which were directly in contact with the treatment solution), but not in leaves [ 22 ]. Cross-talk between SNP and heavy metal Cd led to an increase in AsA amount over single treatments in the green microalga [ 16 ], and cross-talk between SNP and Pb lowered oxidative stress markers and enhanced the antioxidant system in rice [ 23 ], indicating a similar positive effect of SNP in various plant lineages.…”
Section: Resultsmentioning
confidence: 99%
“…Nitric oxide (NO) is a unique simple gaseous molecule, but with considerable impact on plant physiology and metabolism, including adaptations to (heavy) metals [ 19 , 20 ]. It was observed—using NO modulators (donors or scavengers)—that NO often improves metal and Hg-induced negative changes in plants [ 16 , 21 , 22 , 23 ]. However, the role of NO in lichens is less known and only a few studies have reported the impact of NO scavenger under metal excess [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The typical symptoms of essential and nonessential heavy metals in plants include the reduction in root and shoot lengths, the number of tillers per plant, chlorophyll and protein contents, and an increase in the production of reactive oxygen species (ROS), malondialdehyde (MDA), electrolyte leakage (EL), water and nutrients imbalances, chlorosis, and senescence, ultimately resulting in plant death [ 1 , 5 , 6 ]. When a cell is exposed to heavy metals, some cell organelles are impacted, including the cell membrane, nucleus, endoplasmic reticulum, mitochondria, lysosome, enzymes, and metabolites involved in the healing process after injury [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many plants have specialized systems for different metal ions, and they work to compartmentalize these ions to prevent exposure to cells’ most delicate parts [ 10 ]. Other detoxification mechanisms for these metals are now in place, chelating, transporting, sequestering, and detoxifying these metal ions in the plant’s vacuole, serving as a second line of defense [ 5 , 10 ]. Furthermore, in response to heavy metals stress, plants produce hormones, phytochelatins (PCs), metal tolerance proteins (MTPs), metallothionein (MTs) ROS, reactive nitrogen species (RNS), and antioxidants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation